2017
DOI: 10.1177/2042018817732731
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid levels are associated with homeostasis model assessment in obese nondiabetic patients: HOMA and uric acid

Abstract: Background: Hyperuricemia leads to insulin resistance, whereas insulin resistance decreases renal excretion of uric acid. The aim of this study was to evaluate whether there is a correlation between serum uric acid levels with homeostatic model assessment (HOMA) 1 in nondiabetic patients. Methods: We evaluated 88 nondiabetic patients, in whom uric acid levels were measured, in all of them HOMA of β-cell function (HOMA 1B) and HOMA of insulin resistance (HOMA 1IR) scores were performed. Uric acid and the HOMA 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…Therefore, the resultant ADP is further degraded to AMP. In the insulinresistant state (prediabetes), xanthine dehydrogenase enzyme is activated and triggered the conversion of the AMP to uric acid, hence resulting into the observed hyperuricaemia and elevated uric acid excretion in this study [43,44]. Therefore, we suggest that the significant increase in uric acid levels in the plasma may be due to the chronic consumption of fructose diet which triggered insulin resistance and further leads to the observed hyperuricaemia and significant urinary excretion of uric acid in prediabetic control rats (Figure 3(d)).…”
Section: Effects Of Ba Administration With or Without Dietmentioning
confidence: 72%
“…Therefore, the resultant ADP is further degraded to AMP. In the insulinresistant state (prediabetes), xanthine dehydrogenase enzyme is activated and triggered the conversion of the AMP to uric acid, hence resulting into the observed hyperuricaemia and elevated uric acid excretion in this study [43,44]. Therefore, we suggest that the significant increase in uric acid levels in the plasma may be due to the chronic consumption of fructose diet which triggered insulin resistance and further leads to the observed hyperuricaemia and significant urinary excretion of uric acid in prediabetic control rats (Figure 3(d)).…”
Section: Effects Of Ba Administration With or Without Dietmentioning
confidence: 72%
“…Although there is some discrepancy in the way that obesity and metabolic health status were defined, our results were in agreement with previous studies and support a sex-specific difference in the association of MHO with hyperuricemia, that is, only MHO women were at a significant 2-fold higher risk of hyperuricemia compared to their MHNW peers; this association persisted after adjustment for potential confounding factors. Another small sample study, performed by Elizalde-Barrera et al among 88 nondiabetic Mexican patients free of cardiovascular disease, showed a significant correlation between HOMA-IR and SUA in women, especially in obese women, but not in men in general ( 54 ). This also supports our evidence of a sex-specific effect because the metabolic health status can be defined by the HOMA-IR criterion ( 55 ), and more specifically, only obese women with higher HOMA-IR, a surrogate of the MHO phenotype, were significantly positively related to elevated SUA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Methyladenosine has been associated with urinary system cancers and uremia (22) and was reported to decrease (along with alanine, proline, trans-cinnamic acid, tyrosine, and BCAAs) with ≥10% weight loss in obese individuals after a 1-y weightloss program (23). Previous reports in the literature regarding purine catabolism, uric acid, and insulin resistance, especially in obese patients (24), support the role of purine metabolites in the pathophysiology of insulin resistance and T2D. Elevation in the BCAAs valine, leucine, and isoleucine, and in aromatic amino acids, has been previously observed, especially in obesity-related insulin resistance.…”
Section: Discussionmentioning
confidence: 99%